2013
DOI: 10.1021/np400359y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oxygenated Meroterpenoids from Fruiting Bodies of the Mushroom Tricholoma terreum

Abstract: Four new meroterpenoids, terreumols A-D (1-4), with a rare 10-membered ring system, were isolated from the fruiting bodies of Tricholoma terreum. Their structures with absolute stereochemistry were determined by comprehensive spectroscopic methods, as well as single-crystal X-ray diffractions. Compounds 1, 3, and 4 were evaluated for their cytotoxicities against five human cancer cell lines; all of them exhibited inhibitory effects, with IC50 values comparable to those of cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 28 publications
3
36
0
1
Order By: Relevance
“…Plant terpenoids are used widely in traditional herbal remedies and their anti-bacterial, anti-cancerous and other pharmaceutical functions are under investigation [27]. It has been demonstrated that terpenoids extracted from mushrooms possess anti-tumor effects by directly suppressing cancer cell growth and invasion [28]. Among terpenoids, triterpenoids are ones that possess anti-tumor effects, which are mediated through inhibition of tumor cell proliferation and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Plant terpenoids are used widely in traditional herbal remedies and their anti-bacterial, anti-cancerous and other pharmaceutical functions are under investigation [27]. It has been demonstrated that terpenoids extracted from mushrooms possess anti-tumor effects by directly suppressing cancer cell growth and invasion [28]. Among terpenoids, triterpenoids are ones that possess anti-tumor effects, which are mediated through inhibition of tumor cell proliferation and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the proliferation of K562 and HepG2 tumor cells [68] Tricholoma terreum Four meroterpenoids, terreumols A-D Cytotoxicities against five human cancer cell lines [69] Agrocybe aegerita Lectin Inhibition of human and mouse tumor cells via inducing apoptosis [70] Albatrellus confluens Grifolin…”
Section: Mushrooms Bioactive Compound(s) Effects Referencesmentioning
confidence: 99%
“…are reported to be used as a source of immunostimulants, antitumor agents and medicinal adaptogens (Nitha et al 2007). Some compounds extracted from Tricholoma terreum were found to have cytotoxic effects against five human cancer cell lines (Yin et al 2013). Cantharellus cibarius is a beneficial nutrient for human health with high levels of vitamins B and C (Muszynska et al 2013).…”
Section: Introductionmentioning
confidence: 99%